MANAJEMEN KURIKULUM FULL-DAY SCHOOL ANAK USIA DINI DALAM MENINGKATKAN KEPUASAN PELANGGAN STUDI KASUS: KELOMPOK BERMAIN (KB) TK KREATIF PRIMAGAMA YOGYAKARTA TAHUN PELAJARAN 2017/2018 - Fadma Rosita; M. Rudi Gunawan Parozak (LPPM Institut Pendidikan Nusantara Global, 2020)
The purpose of this study is to find out how early childhood curriculum management in Primagama Creative PG Kindergarten in terms of aspects: curriculum planning, curriculum organizing, curriculum implementation at school and class level, and curriculum evaluation. Knowing the inhibiting factors and supporting factors for implementing Full-Day School curriculum. Knowing about the level of customer satisfaction and also the results achieved by graduates of the applied curriculum. This research uses qualitative descriptive research type, with research subjects are teachers, principals, expert staff, and Walagisiwa students of Primagama Creative Kindergarten KB in the academic year 2017/2018. data collection methods using the method of observation, interviews, and documentation. Data validity is done by using data triangulation. Data analysis techniques used in this study were data collection, data reduction, data presentation, and drawing conclusions and testing. The results showed that: 1) curriculum planning was carried out by an academic creative team led by the HR manager. The academic creative team consists of teachers representing each level in each branch. The curriculum is designed based on the development of the curriculum set by the government, namely the 2013 curriculum. 2) Organizing the curriculum is carried out by the HRD manager by selecting HR as seen from the competencies and abilities of each individual. 3) curriculum implementation is done well. The teacher is very creative in implementing the curriculum. Teachers cooperate with each other in implementing the school level curriculum and class level. The implementation is on schedule and in accordance with the curriculum. 4) curriculum evaluation has been done well. From the results of the evaluation conducted, there is still a need for revision or improvement of the curriculum that is being carried out because it is still in the curriculum phase of the 2013 curriculum. It is not necessary to replace the curriculum at this time. 5) the inhibiting factor in the implementation of the curriculum is the difficulty in presenting media from natural materials when learning. The characteristics of the developing child make it difficult for the teacher to condition the class and deliver the material. Factors supporting the implementation of the curriculum in the form of sufficient funds, complete facilities and infrastructure, and good human resource capabilities. 6) the level of customer satisfaction in the 2017/2018 school year has been achieved with the implementation of curriculum management in Primagama Creative Kindergarten KB schools.